Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials